1999
DOI: 10.1002/(sici)1097-0274(199906)35:6<595::aid-ajim7>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of blood lead levels to personal hygiene habits in lead battery workers: Taiwan, 1991-1997

Abstract: Background: The blood lead concentrations of workers in lead battery factories are more than 4 times higher than those of the general population in Taiwan. Therefore, efforts are needed to reduce lead exposure in this high‐risk population. A health promotion program on personal habits that reduce lead exposure has been carried out in a lead battery factory since 1991. This study investigated the longitudinal relationship of workers' blood lead concentrations and personal hygiene habits from 1991 through 1997. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
36
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 17 publications
6
36
1
Order By: Relevance
“…The ingested lead might reduced the relationship of blood lead level to age and airborne lead level. Thus, safety behaviors of workers including personal hygiene should be emphasized 9) . We should have various control measures to decrease blood lead level of workers who exposed to lead.…”
Section: Discussionmentioning
confidence: 99%
“…The ingested lead might reduced the relationship of blood lead level to age and airborne lead level. Thus, safety behaviors of workers including personal hygiene should be emphasized 9) . We should have various control measures to decrease blood lead level of workers who exposed to lead.…”
Section: Discussionmentioning
confidence: 99%
“…We assumed that blood lead levels had gradually increased to this value from the date of hiring. In fact, the industrial hygiene of the plant had changed little until we intervened in 1990 5) ; thus, before 1991, blood lead levels of workers in this plant could be rationally assumed to have reached equilibrium, similar to the first measurement in our laboratory.…”
Section: Lead Exposure Parametersmentioning
confidence: 91%
“…We have been following up a group of lead workers for 12 yr. Although some studies had been done on personal hygiene habits 5) and health effects 6) , we cannot University Hospital, Kaohisiung City, Taiwan-Gene polymorphism is an important factor that affects human susceptibility to toxins. For example, previous studies suggested that the ALAD genotype is an important factor affecting workers' susceptibility to lead toxic effects, including hemopoietic and nervous system.…”
mentioning
confidence: 97%
“…Thus, we suggest that the tasks and behaviors at work which expose workers to lead should be assessed, and correct work practices and safety behaviors of workers including good personal hygiene be encouraged 24) . Various control measures to decrease BLL of workers should be implemented.…”
Section: Implications Regarding Reduction Of Lead Contaminationmentioning
confidence: 99%